The conviction to lead : 25 principles for leadership that matters - Mohler, R. Albert, Jr., 1959- (Minneapolis, Minn. : Bethany House, 2012)
"The president of an influential seminary and media personality reveals the characteristics of a true leader"--Provided by publisher.
Includes bibliographical references (p. 215-220) and index.
Keywords: Leadership; Christian leadership